Assuring availability of sweetpotato planting material: scaling out “Triple S” in northern Uganda - Namanda, S.; Magezi, Sylvia Ruhweza; Biryabaho, S. (International Potato Center, 2015)
Under the five-year HarvestPlus led project ‘Developing and Delivering Biofortified Crops in Uganda’, CIP scientists are leading the component to adapt and refine the technology to local conditions and test a strategy to promote the use of the Triple S at scale. The aim is to reach 30% of the target 1,500 agricultural households in drought-prone project areas of Uganda with this technology by the end of 2016. This flyer describes the approaches used to achieve this target, as well as the progress made between June 2014 and July 2015, the lessons learnt and future plans.